2017
DOI: 10.1016/j.ces.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for detecting and computing univolatility curves in ternary mixtures

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao. b s t r a c tResidue curve maps (RCMs) and univolatility curves are crucial tools for analysis and design of distillation processes. Even in the case of ternary mixtures, the topology of these maps is highly non-trivial. We propose a novel method allowing detection and computation of univolatility curves in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…37 Furthermore, ternary granular mixtures have practical significance too, e.g., the gasification of rice husk can be improved by adding silicon sand and coal; 41 the performance of the ironmaking blast furnace can be improved by charging the fine particles on top of the medium particles to avoid undesired percolation, and large particles to the furnace center to form a strong central gas flow with smooth solid burden discharging; 39 the ternary diethylamine-chloroform-methanol mixture in the separation and distillation industry that gives the unusual univolatility curve. 42 For the rotating drum, ternary-size mixtures received comparatively less attention than binary-size mixtures, although one of the first reports on the axial segregation phenomenon nearly 80 years ago in the rotating drum was based on a ternary-size limestone mixture. 43 By means of DEM, Rapaport 44 numerically studied the axial segregation of a ternary mixture in a rotating drum and found that the axial band formation is such that the medium-size particles tend to be located between the bands of small and large particles.…”
Section: Introductionmentioning
confidence: 99%
“…37 Furthermore, ternary granular mixtures have practical significance too, e.g., the gasification of rice husk can be improved by adding silicon sand and coal; 41 the performance of the ironmaking blast furnace can be improved by charging the fine particles on top of the medium particles to avoid undesired percolation, and large particles to the furnace center to form a strong central gas flow with smooth solid burden discharging; 39 the ternary diethylamine-chloroform-methanol mixture in the separation and distillation industry that gives the unusual univolatility curve. 42 For the rotating drum, ternary-size mixtures received comparatively less attention than binary-size mixtures, although one of the first reports on the axial segregation phenomenon nearly 80 years ago in the rotating drum was based on a ternary-size limestone mixture. 43 By means of DEM, Rapaport 44 numerically studied the axial segregation of a ternary mixture in a rotating drum and found that the axial band formation is such that the medium-size particles tend to be located between the bands of small and large particles.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the volatility order B AE indicates that B is the first possible distillate product in this section. The feasibility region A BE of this class is located in the lower part of the ternary diagram. Similar analysis can be carried out for the volatility orders C AE and C BE. Only when the entrainer flow rate is larger than this minimum value, the separation is feasible and the component A could be obtained at the distillate stream by a direct column configuration.…”
Section: Methodsmentioning
confidence: 85%
“…Such systems occur in nature much more often than systems containing two internal azeotropes (biazeotropic systems). The existence of two internal azeotropes in some binary mixtures was confirmed experimentally and in ternary mixtures just by mathematical modeling. Biazeotropic binary system benzene (B) + perfluorobenzene (PFB) is the most studied one. This mixture is characterized by the complex nature of the phase behavior: the vapor–liquid equilibrium diagram contains two azeotropes (with minimum and maximum boiling points at constant pressure ,, ), the liquid–solid equilibrium diagram contains two eutectic points, and a solid-phase intermolecular complex is formed in mixture B + PFB at room temperature. , No less interesting is the behavior of this system in the presence of water (W).…”
Section: Introductionmentioning
confidence: 94%